Correlation between oxidative stress and tumor grade in glioma cells from patients in Jakarta (Faculty of Medicine Universitas Indonesia, 2012)
Background: The goal of this study was to analyze the correlation of oxidative stress in human glioma cells with tumor grade in order to explore the role of oxidative stress as a marker in determining the tumor progression. Methods: Samples were 21 brain tumors and 5 normal brain tissues from glioma patients. Oxidative stress was analyzed by measuring malondialdehyde (MDA), carbonyl and 8-hydroxy-2’-deoxyguanosine (8-OhdG). Additionaly, we analyzed MnSOD expression by measuring the MnSOD mRNA using real time RT-PCR and MnSOD enzyme activity using RanSOD kit. Tumor grade was determined by histopathologic examination. Data was statistically analyzed using t-test and Pearson correlation. Results: Levels of MDA, carbonyl and 8-OHdG reflecting oxidative stress in glioma cells were significantly higher than in normal brain tissue. The MDA and carbonyl levels were significantly correlated with tumor grade. Relative expression of MnSOD mRNA and specific enzyme activity in glioma cells were significantly higher than in normal brain cells. The relative expression of MnSOD mRNA increased significantly in accordance with the tumor grade. Surprisingly, MnSOD specific activity was significantly lower in high grade than in low grade glioma indicating a discrepancy between mRNA synthesis and its enzyme specific activity. Furthermore, there was a positive correlation between MnSOD mRNA and MDA levels. Conclusion: The high level of oxidative damage in human glioma cells was significantly correlated with tumor grade. The high level of MnSOD expression in human glioma cells was correlated with the high level of oxidative damage. (Med J Indones. 2012;21:122-7)